Does China’s Aid in Africa Affect Traditional Donors? - Deyassa, Kassaye (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
China’s role as an emerging aid provider and the concept of a social plan in Africa has led to polarised responses in the West. Several say that this “productivist” strategy is much less determined by the concepts of citizenship, legal, social rights, and much more regarding building functions. The purpose of this study is to examine whether the welfare and social policy ideas that characterize Chinese aid in Africa are influencing traditional donors and becoming global. The article utilised a qualitative study that has two main components. First, a comprehensive content analysis of over 50 key Sino-African, Chinese and Western policy documents from 2000 (since cooperation between Beijing and African countries first became institutionalised). Second, there were semi-structured interviews with Chinese, African and Western stakeholders in Addis Ababa, (Ethiopia), who was directly involved in the relationship between China and Africa and related development issues. The result of documentation and interview analyses show that there are currently significant differences between Chinese and Western approaches. China has made much stronger and more explicit links between development aid and economic activity than most Western donors. The aid is usually implemented through specific projects rather than broader programs or policies.